A novel isophorone-based red-emitting fluorescent probe for selective detection of sulfide anions in water for in vivo imaging. Issue 15 (29th March 2017) - Huo, Fangjun; Zhang, Yaqiong; Ning, Peng; Meng, Xiangming; Yin, Caixia
Abstract : A new red-emitting fluorescent probe for detection of sulfide anions in living cells (MCF-7 cells) and zebrafish was developed. Abstract : The sulfide anion is significant in industrial processes, biology and environmental science. Hence, robust fluorescent sensors for sulfide which are water soluble and biocompatible are highly desirable. Here, we developed a novel red-emitting fluorescent probe (SP1 ) for the sulfide anion based on cleaving the dinitrobenzenesulfonate ester to restore the fluorescence, accompanied by a long wavelength emission at 644 nm. The detection process took place in 100% PBS buffer, which suggested it had excellent water solubility. Most importantly, the ability ofSP1 to detect sulfide anions in living cells (MCF-7 cells) and zebrafish has also been proven.